2004
DOI: 10.1161/01.str.0000115161.10646.67
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinemia, Oxidative Stress, and Cerebral Vascular Dysfunction

Abstract: A n elevated circulating concentration of the sulfurcontaining amino acid homocysteine, hyperhomocysteinemia, produces complex changes within the blood vessel wall. In the peripheral circulation, these changes include oxidative stress, proinflammatory effects such as expression of tumor necrosis factor-␣ and inducible nitric oxide (NO) synthase (iNOS), and endothelial dysfunction. [1][2][3][4][5][6] Hyperhomocysteinemia-induced oxidative stress may occur as a result of decreased expression and/or activity of k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
151
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(156 citation statements)
references
References 31 publications
2
151
0
3
Order By: Relevance
“…38 Many studies using animal models and human subjects have demonstrated that HHcy induces endothelial dysfunction. 39,40 The degree of impairment of endothelium-dependent relaxation during HHcy is similar to that of other risk factors such as hypercholesterolemia and hypertension. 39 The mechanisms by which HHcy induces endothelial dysfunction are incompletely defined.…”
Section: Hhcy and Endothelial Cell Dysfunctionmentioning
confidence: 95%
See 2 more Smart Citations
“…38 Many studies using animal models and human subjects have demonstrated that HHcy induces endothelial dysfunction. 39,40 The degree of impairment of endothelium-dependent relaxation during HHcy is similar to that of other risk factors such as hypercholesterolemia and hypertension. 39 The mechanisms by which HHcy induces endothelial dysfunction are incompletely defined.…”
Section: Hhcy and Endothelial Cell Dysfunctionmentioning
confidence: 95%
“…41 It is likely, therefore, that HHcy decreases nitric oxide bioavailability through alternative mechanisms, such as accelerated oxidative inactivation of nitric oxide. 40 Homocysteine-induced oxidative inactivation of nitric oxide has been observed in vitro in cultured endothelial cells, 42 and evidence for increased oxidative inactivation of nitric oxide during HHcy has been obtained in animals using both pharmacological 41,[43][44][45][46] and genetic 47,48 approaches. Several types of reactive oxygen species (ROS), including superoxide, hydrogen peroxide, and peroxynitrite, may contribute to the oxidative inactivation of endothelium-derived nitric oxide in HHcy.…”
Section: Hhcy and Endothelial Cell Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Control of folate has a major impact on homosysteine levels, with an inverse relationship between plasma folate and homocysteins levels [11,26]. Many epidemiological studies have related folate deficiency and resultant elevated plasma total homocysteine levels with an increased risk of vascular disease and ischemic stroke [8,11,12,19,26]. Folic acid deficiency and high homocysteine levels can be directly toxic to cultured neurons by mechanisms that involve uracil misincorporation, impaired DNA repair, and DNA damage [20,21,23].…”
Section: Discussionmentioning
confidence: 99%
“…Более того, экспериментальные исследования показывают, что увеличение общего уровня ГЦ усугубляет сосудистые заболевания [47]. В исследовании Han L. с соавт.…”
unclassified